E-commerce and SME performance: The moderating influence of entrepreneurial competencies - Arsalan Hussain; Minhas Akbar; Arfan Shahzad; Petra Poulova; Ahsan Akbar; Rohail Hassan (Administrative Sciences, 2022)
This research aims to examine the mediating role of the use of the e-commerce and moderating influence of entrepreneurial competencies on the performance of small and medium enterprises (SMEs). The study data were collected via a structured questionnaire comprised of a seven-point Likert scale from practitioners serving at the top and middle-level positions in Pakistani SMEs. The Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was applied on 250 useable returned questionnaires. The results showed that the association between the use of e-commerce and firm performance is positively significant. Moreover, the use of e-commerce mediates the positive association between technological readiness, adoption cost, and firm performance. However, the moderating role of entrepreneurial competencies does not appear as significant between the use of e-commerce and manufacturing SMEs' performance. The present study is the first to explore entrepreneurial competencies as a moderator between e-commerce adoption and firm performance. The empirical outcomes of this research provide useful theoretical and practical implications for the managers and practitioners to understand the underlying factors for the successful implementation of e-commerce in the SME sector to enhance firm performance.
Keywords: 350; adoption cost; diffusion of innovation; e-commerce; entrepreneurial competencies; Pakistan; resource-based view; small and medium enterprises; technological readiness